2015
DOI: 10.3928/01477447-20151002-93
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Perforation and Multiple Emboli After Percutaneous Vertebroplasty

Abstract: Percutaneous vertebroplasty is a minimally invasive technique for treating vertebral compression fractures and tumors. Although percutaneous vertebroplasty is considered a relatively safe and technically simple procedure, it is also associated with life-threatening complications as a result of cement leakage, including cardiac perforation and pulmonary embolism. A 63-year-old woman underwent percutaneous vertebroplasty for an L3 vertebral fracture and had cement leaks into the inferior vena cava, pulmonary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“… 4 8) Cement leakage can occur as a complication of cement augmentation and cause local complications and systemic complications such as cerebral embolism, cardiac embolism, pulmonary embolism, renal artery embolism, and acute respiratory distress syndrome. 2 6 7 10 11 13 14 15) The mechanisms of cement leakage have not been analyzed yet, but it could be estimated. First, the intravetebral cleft would be a tract of cement leakage.…”
Section: Discussionmentioning
confidence: 99%
“… 4 8) Cement leakage can occur as a complication of cement augmentation and cause local complications and systemic complications such as cerebral embolism, cardiac embolism, pulmonary embolism, renal artery embolism, and acute respiratory distress syndrome. 2 6 7 10 11 13 14 15) The mechanisms of cement leakage have not been analyzed yet, but it could be estimated. First, the intravetebral cleft would be a tract of cement leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Even though PE is described as a rare complication in dogs undergoing balloon valvuloplasty, 36,37 cardiac perforation always must be taken into consideration as a possible complication. There are several case reports in humans 9,38 and even in dogs 13,19,39 reporting cardiac perforation during catheterisation with or without resulting PE. Iatrogenic perforation of the heart can lead to PE and pericardial tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Complications including hypotension, bradycardia, desaturation, ventricular arrhythmias, ventricular fibrillation, cardiopulmonary arrest and rupture of the balloon catheter have been reported during valvuloplasty in dogs. 8 Cardiac perforation has been reported as a possible but rare complication during balloon valvuloplasty in humans [9][10][11] ; however, to the authors' knowledge, cardiac perforation is reported even more rarely as a possible complication in dogs. 12,13 This case report describes an accidental cardiac perforation with resulting pericardial tamponade and cardiac arrest during advancement of the guiding wire for balloon valvuloplasty in a Coton de Tulear dog.…”
Section: Introductionmentioning
confidence: 99%
“…The localization of puncture points of traditional PVP are not accurate enough, and various kinds of complications are reported now and then. 21,22 How to improve the precision and safety of puncture technology is the key factor to prevent complications from happening.…”
Section: Discussionmentioning
confidence: 99%